Inquiring into Animal Enhancement
XIV, 137 p.
Keywords: This book explores issues raised by past and present practices of animal enhancement in terms of their means and their goals, clarifies conceptual issues and identifies lessons that can be learned about enhancement practices, as they concern both animals and humans.